2004
DOI: 10.1111/j.1365-2389.2004.00639.x
|View full text |Cite
|
Sign up to set email alerts
|

Spatial location of carbon decomposition in the soil pore system

Abstract: We sought to examine the distribution of carbon (C) decomposition within the framework of the soil pore system. Soils were sampled from a transect having a natural gradient in pore-size distribution. After the addition of labelled wheat straw ( 13 C) the repacked soil columns were incubated (25 C) at soil water matric potentials of either À75 kPa or À5 kPa and for either 4 or 90 days. Pore-size distribution was determined for each soil column after incubation and soils were then analysed for soluble C, label-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
109
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 218 publications
(115 citation statements)
references
References 31 publications
6
109
0
Order By: Relevance
“…17.1d) provide a haven for SOM so that a portion of SOC is poorly accessible to microbes or enzymes and thus protected. Calabi-Floody et al (2011) showed that significant SOC, which resisted the treatment of hydrogen peroxide, was strongly held by allophane and imogolite in Andisols, a finding consistent with studies of the physical protection and stabilisation of SOM within larger micro-and macroaggregates (Elliott, 1986;Strong et al, 2004). It is possible that SOC is protected against the attack of enzymes in the narrowest interstices, such as in nanoaggregates, because the diffusion pathway for the passage of enzymes is constrained (McCarthy et al, 2008;Chevallier et al, 2010).…”
Section: Allophane and Carbon Sequestrationsupporting
confidence: 69%
“…17.1d) provide a haven for SOM so that a portion of SOC is poorly accessible to microbes or enzymes and thus protected. Calabi-Floody et al (2011) showed that significant SOC, which resisted the treatment of hydrogen peroxide, was strongly held by allophane and imogolite in Andisols, a finding consistent with studies of the physical protection and stabilisation of SOM within larger micro-and macroaggregates (Elliott, 1986;Strong et al, 2004). It is possible that SOC is protected against the attack of enzymes in the narrowest interstices, such as in nanoaggregates, because the diffusion pathway for the passage of enzymes is constrained (McCarthy et al, 2008;Chevallier et al, 2010).…”
Section: Allophane and Carbon Sequestrationsupporting
confidence: 69%
“…Soil structure is a dynamic hierarchy of aggregates of different sizes that contain microbial cells [34][35][36]53]. Physical structure and geometry of soil pores [40,46,49] dictate how nutrients may penetrate and diffuse within the soil, and spatial heterogeneities can create local variations in substrate availability. This may lead to the formation of preferable residence sites for microbial organisms [36].…”
Section: Introductionmentioning
confidence: 99%
“…This type of protection is largely a function of soil structure, occurring primarily within meso-and microaggregates, pores with spaces or entrances too small for soil organisms or enzymes to pass (Oades 1988;Mayer et al 2004;Strong et al 2004). Additionally, highly tortuous diffusional paths may reduce the viability of bacterial 'foraging' using enzymes, potentially reducing the likelihood that otherwise degradable SOM is degraded (e.g., Vetter et al 1998).…”
Section: Accessibilitymentioning
confidence: 99%